A visual search task to evaluate top-down and bottom-up control of the pre-attentive stage and the ACT-R/PM vision module - Ünlü, Hakan. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2006., 2006)
Visual Attention is deployed in two stages: The pre-attentive stagedetermines which areas of the visual field are relevant for the task and therefore needto be attended. The attentive stage processes the visual information available at the attended portion of the visual field. Two rival views suggest that the pre-attentivestage is controlled by physical properties of the visual field (bottom-up) or the goalsand intentions of the observer (top-down). In support of the bottom-up approach,Theeuwes conducted an experiment to show an irrelevant singleton cannot be masked in a top-down fashion. However Bacon and Egeth (1994) suggested that thenature of the task dictates which method will be used. In this study, threeexperiments were conducted to test Theeuwes̕ Irrelevant Singleton hypothesis andBacon and Egeth̕s Feature Search hypothesis. The results were not compatible with either claim. The experiment results are further analyzed. Data indicate that, search times depend on the color, location, set size and the form (ii) the time spentper item is larger when there is no target in the display; in the presence of atarget, the average search time per item is inversely proportional to the set size. Several possible explanations are discussed. ACT-R/PM is a cognitive architecture that allows a cognitive task to bemodeled in computer environment. One of our experiment setups was modeled in ACT-R/PM to verify that ACT-R/PM can model our task. The results show that,when default parameters are used, ACT-R/PM is slower than human participants. Also, ACT-R models fail to show the inverse relation between average response timeper item and the set size. These results were evaluated and a criticism of current ACT-R/PM constructs was provided.
Keywords: Attention.